General equilibrium dynamics with naïve and sophisticated hyperbolic consumers in an overlapping generations economy - Takeshi Ojima (Osaka University, Institute of Social and Economic Research (ISER), 2013)
Using an overlapping generations model, this paper describes interactions between naïve and sophisticated hyperbolic discounters in general equilibrium. The naïfes, who overestimate their future propensity to save and hence over-forecast the future equilibrium asset prices, are exploited through capital transactions by sophisticates, who correctly forecast the future asset prices by incorporating the naïfes' mis-forecasts. Due to the capital losses, the naïfe fall into bankruptcy when they are highly present-biased, highly patient, and having a low population density. Under generous conditions, the equilibrium is shown to be globally stable and Pareto inefficient in the ex-post sense.
More recent version: http://hdl.handle.net/10419/148186
Keywords: D51; D91; 330; Bankruptcy; Hyperbolic discounting; Naïf; Sophisticate; General equilibrium